PREVALENSI HIPERTENSI PADA PENDUDUK UMUR 30 TAHUN HINGGA 80 TAHUN DI KECAMATAN TEMBUKU BANGLI BALI TAHUN 2013 - I Made Artha Wiguna Sanjaya (Universitas Udayana, 2016)
Hypertension cases at coverage of work of Puskesmas Tembuku is ranked number 9 of 10 major diseases whereby majority of the cases are among people at the age of 30 y.o. to 80 y.o. with the total number of 950 cases (3.50%). Death due to stroke in year 2011 is ranked number 3 with the total number of 11 deaths (5.79%). Lifestyle of the community is one of the factor of hypertension. Method: This research uses quantitative descriptive. Population for this study is the whole community of Tembuku District, Kabupaten Bangli within the age of 30 y.o. to 80 y.o. on June with the total of 961 people ( 39 sampels). Results: Majority of the respondents who suffer from hypertension are above the age of 60 y.o. (53.8%). From the total of 39 sampels, 13 respondents suffer from hypertension, 76.9% consume inadequate amount of fruits, 100% consume inadequate amount of vegetables, 97.4% consumes meat from where 44.7% consume red meat, 33.3% smoke cigarette, 10.2% consume alcoholic drinks and 53.8% do not perform physical activities. Conclusion: Hypertension is found on respondents who consume inadequate amount of fruits (34.5%), respondents who consume inadequate amount of vegetables (39.4%), respondents who consume meat (31.6%), respondents who smoke cigarette (15.4%), respondents who consume alcoholic drinks (25.0%) and respondents who do not perform physical activities (42.9%). The result of this research shows there is a tendancy of hypertension based on lifestyle.